The Effectiveness of School Operational Assistance Fund (Bos) Distribution in SD Negeri Girirejo 02 Ngablak Magelang Regency - Rinda, Rinda Herdiyani; Joko Raharjo, Tri; Soesilowati, Etty (Educational Management, 2019)
This study aims to describe the planning, implementation, supervision, evaluation and reporting and accountability of the management of school operational assistance fund in SDN Girirejo 02 Ngablak, Magelang Regency. Data were collected by interview, questionnaire and documentation, which were then analyzed by quantitative descriptive analysis. The results showed that the preparation of the RKAS was on schedule at the beginning of the fiscal year, based on the priority scale of school needs, and involved committees and teachers. The implementation aspect was not entirely successful because the distribution of BOS fund was still too late. Bookkeeping administration was in accordance with Permendiknas No. 48 of 2017. The aspect of supervision was still unsuccessful because there was no supervision from the school committee and related agencies on a regular basis. Evaluation activities by the committee had been conducted even though they had not been maximized. Reporting on the management of BOS fund in SDN Girirejo 02 can be said that it had been successful because it had made a report in accordance with the technical guidelines for managing BOS funds in accordance with Ministry of Education Regulation No.48 2017. The effectiveness of BOS fund management at SD Negeri Girirejo 02 reaches 63%, within the effective criteria.